2013
DOI: 10.3758/s13415-012-0144-4
|View full text |Cite
|
Sign up to set email alerts
|

Perceived ownership impacts reward evaluation within medial-frontal cortex

Abstract: Ownership is a powerful construct. Indeed, in a series of recent studies, perceived ownership has been shown to increase attentional capacity, facilitate a memorial advantage, and elicit positive attitudes. Here, we sought to determine whether self-relevance would bias reward evaluation systems within the brain. To accomplish this, we had participants complete a simple gambling task during which they could "win" or "lose" prizes for themselves or for someone else, while electroencephalographic data were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 39 publications
(45 reference statements)
4
30
0
Order By: Relevance
“…In line with previous work (e.g., Krigolson et al, 2013, 2014), ERP components were measured based on visual inspection of grand-average waveforms ( Figures 3, 4, 7, 8 ) and associated scalp topographies ( Figures 5, 9 ). Visual inspection revealed that the peak difference between hits and misses (i.e., the ERN) occurred at fronto-central electrode site FCz.…”
Section: Methodsmentioning
confidence: 90%
“…In line with previous work (e.g., Krigolson et al, 2013, 2014), ERP components were measured based on visual inspection of grand-average waveforms ( Figures 3, 4, 7, 8 ) and associated scalp topographies ( Figures 5, 9 ). Visual inspection revealed that the peak difference between hits and misses (i.e., the ERN) occurred at fronto-central electrode site FCz.…”
Section: Methodsmentioning
confidence: 90%
“…propose that perception of value is sensitive to perceived ownership -when gambling OWNERSHIP AND VALUE for another, differences in value are not processed by the medial-frontal system (Holroyd & Coles, 2002;Krigolson et al, 2013;Miltner et al, 1997) and are ignored, or are at least affected less relative to when one gambles for oneself.…”
Section: Discussionmentioning
confidence: 99%
“…This system is differentially sensitive to wins and losses, and is especially active when feedback is unexpected. To explore the interaction between medial-frontal feedback processing and ownership, Krigolson, Hassall, Balcom, and Turk (2013) had participants complete a series of gambles within which they either won "prizes" for themselves or for another while electroencephalographic (EEG) data were recorded. Interestingly, the authors found that while there was a difference in the human ERP when wins and losses for oneself were contrasted, this difference was not present when participants were gambling for another.…”
Section: Introductionmentioning
confidence: 99%
“…As stated in the paragraph above, differences between decisions for others and decisions for oneself have been attributed to a decreased emotional engagement when the outcomes affect another person. This assumption of decreased emotional engagement is supported by neuroimaging studies showing a decreased activation of reward‐related brain areas in choices for others compared with choices for the self (Albrecht et al, ; Krigolson, Hassall, Balcom, & Turk, ). Additionally, differences between decisions made for oneself versus others seem to be larger the greater the affective involvement of the participant (Albrecht et al, ).…”
Section: Introductionmentioning
confidence: 88%